2006
DOI: 10.1007/s00167-006-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic proximal tibiofibular joint dislocation treated by open reduction and temporary fixation: a case report

Abstract: Isolated dislocations of the proximal tibiofibular joint are a rare condition. Missed diagnosis can lead to chronic knee pain and disability. Early recognition should be followed by immediate closed reduction or open reduction and joint transfixation. We present a young athlete with this injury which was treated successfully by open reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 6 publications
1
44
0
Order By: Relevance
“…Most dislocations can be treated through closed reduction; however, open reduction may be required in some cases due to an anterior muscle tension and/or interposition of disrupted capsular ligaments that may resist reduction 9. MacGiobain et al 8 and Robinson et al 10 also reported a case of open reduction and internal fixation after an initial attempt with closed reduction failed. MacGiobain et al 8 reported the removal of the K wire 6 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most dislocations can be treated through closed reduction; however, open reduction may be required in some cases due to an anterior muscle tension and/or interposition of disrupted capsular ligaments that may resist reduction 9. MacGiobain et al 8 and Robinson et al 10 also reported a case of open reduction and internal fixation after an initial attempt with closed reduction failed. MacGiobain et al 8 reported the removal of the K wire 6 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The rotational movements of PTFJ happen during the ankle movements, while the knee flexion fibular head moves forward [2,22]. According to the literature, a traumatic dislocation of PTFJ most frequently occurs during playing soccer [23], rarely volleyball [16], skiing [23], basketball [24], trampoline jumping [25], or it results from high-energy trauma as usually seen in polytraumatised patients [26], while it is an extremely rare traumatic dislocation as a result of congenital connective tissue weakness [27]. The ligament reinforcement produces stability in the extended knee, so the injuries of this joint generally occur during knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Most dislocations can be reduced closed; however, open reduction may be necessary as anterior muscle tension and/or interposition of disrupted capsular ligaments may resist reduction. Acute dislocations undergoing open reduction require temporary joint stabilisation with either Kirschner wires [11] or screw fixation [6,12] combined with primary repair of the torn capsule and injured ligaments. Removal of the transfixing wire or screw is necessary to avoid fatigue fracture of the material.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended full weight bearing but avoiding knee flexion beyond 90°. Robinson et al [6] recommended an above knee plaster for 6 weeks non-weight bearing whilst Rajkumar and Schmitgen [5] recommended a cylinder cast for 3 weeks partial weight bearing followed by a knee brace for 3 weeks. Removal of the temporary fixation in these cases was performed between 6 and 12 weeks from the index procedure [6,11,12].…”
Section: Discussionmentioning
confidence: 99%